CREATIVE ECONOMIC EMPOWERMENT THROUGH ECOPRINT TRAINING FOR PKK CADRES AS A DRIVER OF FAMILY ECONOMY IN SAYAR SUBDISTRICT TAKTAKAN SERANG - Ina Khodijah; Raden Irna Afriani; Yuliah Yuliah; Yollanda Octavitri (International Journal of Engagement and Empowerment, 2021)
Program  community service aims      to  initiate  the  creative  economy of  the community  in the Village  Sayar  Taktakan  District Serang  city,  especially  for  pkk  cadres as the driver of  the family economy.  The program was held by a team of  lecturers from the Faculty of Economics  and  Business, Bina Bangsa   University. This form of  program    is  to provide  ecoprint  training  for  pkk cadres  of Sayar Village.  The training  started from the provision  of  materials  about  ecoprint,    tips  -  tips to  become  an entrepreneur,  recording  financial  statements in the  family  and  business  environment  and  a  good way of  speaking in establishing  communication  in  business  relations  by  a team of  Lecturers  bina bangsa university and Banten Shipping   Polytechnic.   then  continued  with the  process  of making  ecoprint  with  several  stages. The  first stage is  the mordanting process, the second stage  is leaf treatment, the third stage  is the process of leaf  motif  /  leaf  printing, the fourth stage is the steaming  stage, the fifth   stage  is the color  locking  stage  and  the sixth   stage is the final  stage  until  the  ecoprint results are  ready  for  sale.   The ecoprint training  is to improve  the skills of productive age  PKK  members  in  Sayar village  berbasis creative economy. Through this ecoprint training  is  expected to  be the birth of new female entrepreneurs to improve the family economy  and  to  support  their  lives  for the  better   in the future